Pembelajaran Berbasis Kearifan Lokal sebagai Media untuk Membentuk Karakter Siswa Sekolah Menengah Pertama melalui Dongeng dan Fabel - Junifer Siregar; Rahayu Pristiwati; Agus Nuryatim (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2025)
This study examines the role of local wisdom-based learning as a pedagogical medium for shaping student character through fairy tales and fables. The research is grounded in concerns regarding the diminishing integration of moral and cultural values in formal education and addresses how narrative-based local wisdom can contribute to character education. Using a qualitative approach with a literature review (library research), the study analyzes fairy tales sourced from the Solopos Daily and fables developed in the form of digital comics, complemented by direct classroom observations of storytelling practices. Data were collected through documentation, observation, and systematic review of relevant literature. The findings demonstrate that fairy tales and fables grounded in local wisdom are effective media for character formation, as they convey moral values in an engaging and contextually meaningful manner. The narratives examined embody key character values such as discipline, perseverance, tolerance, religiosity, mutual cooperation, honesty toward parents, humility, and childlike sincerity. The study argues that integrating local wisdom-based narratives into learning activities not only supports character education but also contributes to the preservation of cultural heritage. Therefore, fairy tales and fables represent a culturally relevant and pedagogically effective medium for fostering students’ moral and personal development in contemporary education.